PENGARUH LABA KONSERVATISMA TERHADAP RETURN SAHAM: SIZE DAN GROWTH SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS DI BURSA EFEK INDONESIA) - Gunawan, Barbara (Jurnal Analisis Bisnis Ekonomi, 2009)
This study aimed to test the effect of earnings conservatism of the company stock return moderated by variable size and growth. Using a purposive sampling method, the subjects in this study is that there is a manufacturing company in Indonesia Stock Exchange (BEI) of 888 companies. The data comes from the manufacturing company's financial statements and the Indonesian Capital Market Directory (ICMD) for fiscal year ended December 31, 1998 until December 31, 2006 using regression analysis. The results showed that: first, the slope of the regression coefficient of return higher profits for companies with negative returns (bad news) than for firms with positive returns (good news), which means that the average manufacturing firm's profit is conservative. Second, the Company and the Price to Book Ratio (P / B) tend to have low profit, conservative. Third, the moderating influence of size and growth to strengthen earnings conservatism of the company stock return.i